2020
DOI: 10.1186/s12875-020-01283-x
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a clinical diagnostic tool to differentiate multiple myeloma from bone metastasis in patients with destructive bone lesions (MM-BM DDx)

Abstract: Background Most patients with destructive bone lesions undergo a comprehensive diagnostic procedure to ensure that proper treatment decisions are pursued. For patients with multiple myeloma, this can lead to delays in diagnosis and treatment initiation. This study was conducted to develop a diagnostic rule that could serve as a tool for early identification of multiple myeloma and promote timely referral of patients to haematologists. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Six university-affiliated hospitals and medical schools participated in this study: Faculty of Medicine, Chiang Mai University, Khon Kaen University, Siriraj Hospital at Mahidol University, Queen Savang Vadhana Memorial Hospital, Khon Kaen Hospital, and Chulabhorn Hospital. The development dataset of the MM-BM DDx model, 10 including patients diagnosed with either MM or BM at Chiang Mai University Hospital from 2012 to 2015, was also utilized during this external validation to help interpret the findings. 12 The Institutional Review Board of each center approved the study protocol (FAM-2564-07951) and waived the requirement of informed consent due to the retrospective nature of data collection.…”
Section: Source Of Data and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six university-affiliated hospitals and medical schools participated in this study: Faculty of Medicine, Chiang Mai University, Khon Kaen University, Siriraj Hospital at Mahidol University, Queen Savang Vadhana Memorial Hospital, Khon Kaen Hospital, and Chulabhorn Hospital. The development dataset of the MM-BM DDx model, 10 including patients diagnosed with either MM or BM at Chiang Mai University Hospital from 2012 to 2015, was also utilized during this external validation to help interpret the findings. 12 The Institutional Review Board of each center approved the study protocol (FAM-2564-07951) and waived the requirement of informed consent due to the retrospective nature of data collection.…”
Section: Source Of Data and Participantsmentioning
confidence: 99%
“…7 In 2020, a diagnostic tool to differentiate MM from BM in patients with destructive bone lesions (MM-BM DDx) was developed in a large series of patients diagnosed with MM and BM in northern Thailand. 10,11 The model includes three simple, routinely available laboratory parameters: serum creatinine, serum globulin, and serum alkaline phosphatase (ALP). The model demonstrated excellent discriminative ability and calibration.…”
Section: Introductionmentioning
confidence: 99%
“…A large retrospective study 18 18 A recent comparative study including 440 MM and 461 solid metastases suggested that serum ALP can be a useful discriminating marker in presence of bone lesions. A lower or near normal ALP (123.8 ± 79.8 U/L) was associated with MM irrespective of clinical stage and/or number of bone lesions compared to higher levels in solid metastases (p < 0.05).…”
Section: Crab (Hypercalcemia [C] Renal Dysfunction [R] Anemia [A] Bon...mentioning
confidence: 99%
“…This is followed by serum protein electrophoresis for M-band and urinary Bence-Jones protein detection. Subsequently, β-2 microglobulin and serum albumin are used to determine the stage of MM [ 4 , 5 ]. However, these diagnostic tools have proven insufficient for detecting the early stages of MM, with most cases only being identified in the late stages.…”
Section: Introductionmentioning
confidence: 99%